Measurement of CP asymmetries in Λ0b → ph− decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review, 2025)
A search for 𝐶⁢𝑃 violation in Λ0𝑏 →𝑝⁢𝐾− and Λ0𝑏 →𝑝⁢𝜋− decays is presented using the full Run 1 and Run 2 data samples of 𝑝⁢𝑝 collisions collected with the LHCb detector, corresponding to an integrated luminosity of 9 fb−1 at center-of-mass energies of 7, 8, and 13 TeV. For the Run 2 data sample, the 𝐶⁢𝑃-violating asymmetries are measured to be 𝐴𝑝⁢𝐾−𝐶⁢𝑃 =(−1.4 ±0.7 ±0.4)% and 𝐴𝑝⁢𝜋−𝐶⁢𝑃 =(0.4 ±0.9 ±0.4)%, where the first uncertainty is statistical and the second is systematic. Following significant improvements in the evaluation of systematic uncertainties compared to the previous LHCb measurement, the Run 1 dataset is reanalyzed to update the corresponding results. When combining the Run 2 and updated Run 1 measurements, the final results are found to be 𝐴𝑝⁢𝐾−𝐶⁢𝑃 =(−1.1 ±0.7 ±0.4)% and 𝐴𝑝⁢𝜋−𝐶⁢𝑃 =(0.2 ±0.8 ±0.4)%, constituting the most precise measurements of these asymmetries to date.